Tax Revenue Achievement: Between Tax Amnesty and the Voluntary Disclosure Program at KPP Pratama Batu - Ritma Fajar Rosida; Muhammad Hasyim Ashari (International Journal of Economic Research and Financial Accounting, 2024)
his research aims to determine the number of taxpayers who participated in the Tax Amnesty Program and the Voluntary Disclosure Program as well as the tax revenue achievements from these two programs at KPP Pratama Batu along with factors inhibiting the success of the two programs. This research is a descriptive comparative quantitative research using secondary data from KPP Pratama Batu. The data analysis technique uses the Mann-Whitney test. The research results show that as many as 7.72% of the number of registered taxpayers in 2017 at KPP Pratama Batu participated in the Tax Amnesty program by contributing 36.1 trillion or 30% of the total tax revenue in 2017 at KPP Pratama Batu. Meanwhile, 1.30% of the number of registered taxpayers in 2022 at KPP Pratama Batu participated in the Voluntary Disclosure Program by contributing 31.1 trillion or 20% of the total tax revenue in 2022 at KPP Pratama Batu. This shows that there is a difference between the Tax Amnesty Program and the Voluntary Disclosure Program (PPS) at KPP Pratama Batu. Meanwhile, the inhibiting factors for the Tax Amnesty Program and the Voluntary Disclosure Program are high rates and less effective methods of conveying program information to taxpayers.